President Joko Widodo’s Speech Acts in His Viral Video Visiting Lampung - Situmorang, Evelyn; Onggatta, Reggina; Hamzah, Syifa; Rangkuti, Rahmadsyah (TALENTA, 2023)
Politicians utilize a variety of speech acts to achieve specific goals and engage with their audiences through political speeches, interviews, or social media posts that can persuade, convince, or mobilize the public. The objective of this research is to find out the types of speech acts done by President Joko Widodo in his viral interview video visiting Lampung and to examine the effects of each speech act caused. This research applied Austin and Searle’s theory to analyze the locutionary, illocutionary, and perlocutionary acts that the utterances possessed. In this article, the data were analyzed using the qualitative-descriptive method and were taken from the Sekretariat Presiden YouTube Channel. The result findings of this study indicate that President Joko Widodo, as a political leader, used all types of illocutionary acts as yet he tends to use commissive illocutionary speech acts that are essential for him to make promises and prove it in order to show his work and also to appease the citizens in Lampung.